Directions for optimization of legal regulation of social protection of notaries in Ukraine - Багрій, В. А. (Київський національний університет імені Тараса Шевченка, 2025)
In the article the current problem of insufficient efficiency and fragmentation of legal regulation of social protection of notaries in Ukraine is examined. It is argued that in the context of the transformation of Ukraine's social policy, especially taking into account the European integration vector, the issue of forming an effective and comprehensive system of social protection of notaries acquires special importance in order to provide notaries with appropriate social guarantees. An analysis of scientific works in the field under study, as well as the Concept of Reforming Notary Bodies and the Law of Ukraine "On Notaries" is carried out. The shortcomings and gaps of the legislator in the legal regulation of social protection of notaries in Ukraine are emphasized. Based on the Concept of Reforming Notary Bodies, it was established that despite the declared need to update social legislation in the field of notarial activities, the measures provided for in it were not implemented systematically and fully in practice, which, as a result, created a gap between the theoretical principles of reform and the lack of legal implementation results. The article presents a number of substantiated legislative proposals on the legal regulation of social protection of notaries. In particular, a clear proposal has been developed to amend Article 16 of the Law of Ukraine “On Notaries” in order to specify the list of social rights of notaries and the responsibilities of the Notarial Chamber of Ukraine in this area. It also emphasizes the need to develop and adopt a special subordinate regulatory legal act - “Regulations on Social Guarantees of Notaries in Ukraine”, which would specify and detail the mechanisms for implementing the social rights of notaries. It is also proposed to supplement the Law of Ukraine “On Notaries” with a separate chapter devoted to social protection, with the allocation of articles on pension, medical care, insurance, disability, etc. A comprehensive list of areas for optimizing the legal regulation of social protection of notaries in Ukraine has been formulated. It is concluded that the existing model of social protection of notaries in Ukraine is unbalanced, incomplete and not coordinated with other regulatory legal acts in the field of social security.

У статті досліджено актуальну проблему недостатньої ефективності та фрагментарності правового регулювання соціального захисту нотаріусів в Україні. Аргументовано, що в умовах трансформації соціальної політики України, особливо з урахуванням євроінтеграційного вектора, питання формування дієвої і цілісної системи соціального захисту нотаріусів набуває особливого значення з метою забезпечення нотаріусів належними соціальними гарантіями. Здійснено аналіз наукових праць у досліджуваній сфері, а також Концепції реформування органів нотаріату й Закону України «Про нотаріат». Наголошено на недоліках і прогалинах законодавця щодо правового регулювання соціального захисту нотаріусів в Україні. На підставі Концепції реформування органів нотаріату встановлено, що попри задекларовану необхідність оновлення соціального законодавства у сфері нотаріальної діяльності, передбачені у ній заходи не були реалізовані системно та повно на практиці, що, як наслідок, створило розрив між теоретичними засадами реформування і відсутністю правореалізаційних результатів. У статті наведено низку обґрунтованих законодавчих пропозицій щодо правового регулювання соціального захисту нотаріусів. Зокрема, розроблено чітку пропозицію щодо внесення змін до статті 16 Закону України «Про нотаріат» з метою конкретизації переліку соціальних прав нотаріусів і обов’язків Нотаріальної палати України у цій сфері. Також наголошено на необхідності розроблення й ухвалення спеціального підзаконного нормативно-правового акту - «Положення про соціальні гарантії нотаріусів в Україні», який би конкретизував і деталізував механізми реалізації соціальних прав нотаріусів. Також запропоновано доповнити Закон України «Про нотаріат» окремою главою, присвяченою соціальному захисту, з виокремленням статей щодо пенсійного, медичного забезпечення, страхування, непрацездатності тощо. Сформульовано комплексний перелік напрямів оптимізації правового регулювання соціального захисту нотаріусів в Україні. Підсумовано, що наявна модель соціального захисту нотаріусів в Україні є незбалансованою, неповною та не узгодженою з іншими нормативно-правовими актами у сфері соціального забезпечення.
Напрями оптимізації правового регулювання соціального захисту нотаріусів в Україні
Keywords: optimization; notary; legal regulation; social protection; social security; notarial activities.; оптимізація; нотаріус; правове регулювання; соціальний захист; соціальне забезпечення; нотаріальна діяльність.